A proof of concept infant-microbiota associated rat model for studying the role of gut microbiota and alleviation potential of Cutibacterium avidum in infant colic - Rocha Martin, Vanesa Natalin; Del’Homme, Christophe; Chassard, Christophe; Schwab, Clarissa; Braegger, Christian; Bernalier-Donadille, Annick; Lacroix, Christophe (Frontiers in Nutrition, 2022)
Establishing the relationship between the gut microbiota and host health has become a main target of research in the last decade. Human gut microbiota associated-animal models represent one alternative to human research, allowing for intervention studies to investigate causality. Recent cohort and in vitro studies proposed an altered gut microbiota and lactate metabolism with excessive H2 production as main causes of infant colic. To evaluate infant gut microbiota H2 production and to test modulation of gut colonizer lactose- and lactate-utilizer non-H2-producer, Cutibacterium avidum P279, we established and validated a gnotobiotic model using young germ-free rats inoculated with fecal slurries from infants younger than 3 months. Here we show that infant-microbiota associated (IMA) rats inoculated with fresh feces from healthy (n=2) and colic infants (n=2) and fed infant formula, acquired and maintained similar quantitative and qualitative fecal microbiota composition compared to the individual donor’s profile. We observed that IMA rats excreted high levels of H2, which were linked to high abundance of lactate-utilizer H2-producer Veillonella. Supplementation of C. avidum P279 to colic IMA rats reduced H2 levels compared to animals receiving placebo. Taken together, we report high H2 production by infant gut microbiota, which might be a contributing factor for infant colic, and suggest potential of C. avidum P279 to reduce abdominal H2 production, bloating and pain associated to excessive crying in colic infants.